INOVASI MEDIA PEMBELAJARAN BAHASA INDONESIA DALAM IMPLEMENTASI KURIKULUM MERDEKA BELAJAR - Liana Komalasari; Handi Ilham Hamdani; Salman Alfarizsky; Nurfitria (Bajang Institute, 2024)
Innovation of Indonesian language learning media in the independent curriculum which is a means of infrastructure for teachers, students and all parties in developing student competency which makes Indonesian language learning media not rigid, monotonous and boring. Through this research method, we found many innovative Indonesian language learning concepts in the independent learning curriculum in elementary schools which can be applied in schools by teaching staff, in order to be able to create learning activities that are conducive, effective, creative and innovative and easy to accept and understand by students. . Even though there are several challenges regarding the implementation of this learning media innovation, in the end the resulting learning can make it easier for various parties, both teachers and students.